2011
DOI: 10.1161/strokeaha.110.607739
|View full text |Cite
|
Sign up to set email alerts
|

Association Between VEGF Polymorphisms and Homocysteine Levels in Patients With Ischemic Stroke and Silent Brain Infarction

Abstract: Background and Purpose-Vascular endothelial growth factor (VEGF) plays a role in atherosclerosis-related diseases such as cerebrovascular or cardiovascular diseases. However, the effect of VEGF -2578CϾA, -1154GϾA, -634GϾC, and 936CϾT polymorphisms on the susceptibility to stroke and silent brain infarction has not been reported. Methods-Using polymerase chain reaction-amplified DNA, VEGF polymorphisms were analyzed in 615 patients with ischemic stroke, 376 patients with silent brain infarction, and 494 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 79 publications
1
25
1
1
Order By: Relevance
“…In fact, the AGG haplotype was showed to express less VEGF than CGG haplotype [41]. Moreover, the AGG haplotype was associated with stroke [42] and affected the ejection fraction in hypertensive patients with left ventricular hypertrophy [25]. Taking these findings into consideration, we could speculate that a reduced VEGF expression could increase the risk for cardiovascular damages in AGG haplotype carriers through mechanisms suggested by experimental studies [16,43].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the AGG haplotype was showed to express less VEGF than CGG haplotype [41]. Moreover, the AGG haplotype was associated with stroke [42] and affected the ejection fraction in hypertensive patients with left ventricular hypertrophy [25]. Taking these findings into consideration, we could speculate that a reduced VEGF expression could increase the risk for cardiovascular damages in AGG haplotype carriers through mechanisms suggested by experimental studies [16,43].…”
Section: Discussionmentioning
confidence: 99%
“…The CC genotype was also associated with an impaired prognosis in the patients with chronic heart failure (21), the development of heart failure following myocardial infarction (23), AMI (15) and coronary collaterals in the patients with CAD (26) and coronary atherosclerosis (25). The -634 variant genotypes (GC and CC) in the patients with silent brain infarction were significantly lower than those in the controls (24), whereas the G allele of -634G>C polymorphism was significantly higher in the patients with Kawasaki disease with coronary artery lesions (CAL) than in those without CAL or control subjects (32). Moradzadegan et al (33) reported Adjusted by age and gender; b significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Total genomic DNA was prepared from whole blood following the lysis of red blood cells. The areas spanning the polymorphic sites of -634G>C in the 5'-untranslated region (UTR) and 936C>T in the 3'-UTR of the VEGF gene were amplified by the polymerase chain reaction from the genomic DNA using primers and reaction conditions described previously (24). The -634G>C and 936C>T polymorphisms were identified following the digestion of amplified DNA with the endonucleases, AvaII and NlaIII, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Based on clinical manifestations and neuroimaging data, two neurologists classified ischemic stroke into 3 etiological subtypes using the criteria from the Trial of Org 10172 in Acute Stroke Treatment (TOAST) clinical trial as follows (22): i) subtype 1: LAD, an infarct lesion of ≥15 mm in diameter, as determined by an MRI, and significant (>50%) stenosis of a major brain artery or a branch cortical artery, as determined by cerebral angiography, with symptoms associated with that arterial territory; ii) subtype 2: SVD, an infarct lesion of <15 mm, but >5 mm in diameter, as determined by an MRI, and classic lacunar syndrome without evidence of cerebral cortical dysfunction or a potentially detectable cardiac source for the embolism; and iii) subtype 3: CE, arterial occlusions presumably due to a heart-originated embolus, as detected by cardiac evaluation. We measured clinical parameters, including hypertension, diabetes, hyperlipidemia, homocysteine levels, folate levels, vitamin B12 levels, cholesterol, platelet (PLT) count, PT, prothrombin time (PT), activated partial thromboplastin time (aPTT), fibrinogen levels, antithrombin levels, BUN levels and uric acid levels based on previously described methods (23,24).…”
Section: Methodsmentioning
confidence: 99%